CRISPR-mediated rapid generation of neural cell-specific knockout mice facilitates research in neurophysiology and pathology - Xiao, Dan (Mol Ther Methods Clin Dev, 2021)
Inducible conditional knockout mice are important tools for studying gene function and disease therapy, but their generation is costly and time-consuming. We introduced clustered regularly interspaced short palindromic repeats (CRISPR) and Cre into an LSL-Cas9 transgene-carrying mouse line by using adeno-associated virus (AAV)-PHP.eB to rapidly knockout gene(s) specifically in central nervous system (CNS) cells of adult mice. NeuN in neurons and GFAP in astrocytes were knocked out 2 weeks after an intravenous injection of vector, with an efficiency comparable to that of inducible Cre-loxP conditional knockout. For functional testing, we generated astrocyte-specific Act1 knockout mice, which exhibited a phenotype similar to mice with Cre-loxP-mediated Act1 knockout, in an animal model of multiple sclerosis (MS), an autoimmune disorder of the CNS. With this novel technique, neural cell-specific knockout can be induced rapidly (few weeks) and cost-effectively. Our study provides a new approach to building inducible conditional knockout mice, which would greatly facilitate research on CNS biology and disease.